TRYPANOSOMES, A BLOOD PARASITE OF RAJIDAE (ELASMOBRANCHII, RAJIFORMES) OFF THE ALGERIAN COAST. - Sabrina Kefil 1,2*, Safia Abla 1, Chahinez Bouguerche 3, Katia Yata 1, Philippe Grellier 4, Nadia Kechemir-Issad 2. (Chelonian Research Foundation, 2024)
Trypanosomes were found from the blood of tow rajidean fishes (Raja miraletus and Raja asterias) off the central Algerian coast. We described shortly and illustrated this blood protozoan parasites, based on morphological characters. Light microscopy and Immunofluorescence were used for the observation and study of these parasites. Drawings were scanned and redrawn with Adobe Illustrator CS5.1. Specific characteristics such as and morphometric measurements are within the ranges given in previous description by Laveran and Mesnil 1904 of rajidean trypanosomes. Unfortunately, there is no vouchers available for comparison of rajidean Trypanosoma of the type host. Thus, as hosts are different, and localities are widely separated. This is the first record of Trypanosoma off Algerian cost. KEY WORDS: -Protozoans, Parasites, Trypanosoma, Mediterranean Sea, Rajidae.